Bank heterogeneity and capital allocation: Evidence from "fracking" shocks - Matthew C. Plosser (Federal Reserve Bank of New York, 2014)
This paper empirically investigates banks' investment allocations over the recent business cycle. I identify unsolicited deposit shocks resulting from unconventional energy development and estimate bank allocations of these deposits. In the pre-recession period, banks lend 38 percent of incremental deposits; however, during the downturn, banks favor liquid assets and lending allocations fall to 22 percent. Banks with low risk tolerance or less access to liquidity are particularly sensitive to the decline in economic conditions, choosing securities and cash, respectively. The findings identify significant heterogeneity in the willingness of banks to allocate capital during adverse times.
Keywords: G21; E32; 330; financial intermediation; banks; business cycles